The melting points of the inert gas solids - Dunne, Lawrence J. (Array, 2008)
Summary: The melting points of the heavy inert gases and of some other simple molecules show an excellent linear correlation with the depths of their diatomic potential wells, and the slope of the correlation line is in accord with Lindemann's theory of melting